Inter-Rater Reliability of the Qualitative Analysis of the One-Leg Squat Test in Adolescent Athletes - Tekin, Ebru; Unver, Fatma; Güven, Sibel; Orhan, Büşra Nur (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2025)
This study aimed to evaluate the inter-rater reliability of the qualitative analysis of the one-leg squat test in adolescent athletes. The sample consisted of 20 adolescent athletes aged 10 to 18 years with no balance-affecting health issues. The athletes performed the one-leg squat test, and their performances were video recorded. Three raters—a senior physiotherapist, a junior physiotherapist, and a sports scientist—independently evaluated the videos using Lee Herringtonʼs qualitative analysis framework. Fleissʼ Kappa analysis showed no significant agreement among the three raters for the right leg, while a low but significant agreement was found for the left leg (k=0.159, p=0.003). Cohenʼs Kappa analysis indicated no significant agreement between the senior physiotherapist and the sports scientist (k=0.026, p=0.761) or between the junior physiotherapist and the sports scientist (k=0.059, p=0.509). However, a low yet statisticallysignificant agreement was observed between the senior and junior physiotherapists (k=0.250, p=0.008).  The findings suggest that the qualitative analysis of the one-leg squat test does not show strong inter-rater reliability across different professional groups. The low agreement between physiotherapists, despite their experience differences, might be due to similar professional training and perspectives.
Keywords: Qualitative; One-Leg Squat; Reliability